Perception of the Potential for Interaction in Social Scenes - Hessels, Roy S.; Benjamins, Jeroen S.; van Doorn, Andrea J.; Koenderink, Jan J.; Hooge, Ignace T. C. (i-Perception (London), 2021)
In urban environments, humans often encounter other people that may engage one in interaction. How do humans perceive such invitations to interact at a glance? We briefly presented participants with pictures of actors carrying out one of 11 behaviors (e.g., waving or looking at a phone) at four camera-actor distances. Participants were asked to describe what they might do in such a situation, how they decided, and what stood out most in the photograph. In addition, participants rated how likely they deemed interaction to take place. Participants formulated clear responses about how they might act. We show convincingly that what participants would do depended on the depicted behavior, but not the camera-actor distance. The likeliness to interact ratings depended both on the depicted behavior and the camera-actor distance. We conclude that humans perceive the “gist” of photographs and that various aspects of the actor, action, and context depicted in photographs are subjectively available at a glance. Our conclusions are discussed in the context of scene perception, social robotics, and intercultural differences.